Asignación presupuestaria para protección ambiental y su relación con la calidad del gasto público en el Gobierno Regional de Loreto, periodo 2010 – 2022 - Valera Flores, José Alfredo (2025)
This study investigates the relationship between the budget allocation for environmental protection and the quality of public spending in the Regional Government of Loreto during the period 2010-2022. In a context of growing environmental concern at a global and regional level, with Latin America experiencing a notable increase in pollution that negatively affects both the environment and quality of life, the study focuses on the region of Loreto, Peru, known for its rich biodiversity and natural resources. The objective is to understand how the Regional Government of Loreto has managed environmental spending and evaluate whether this spending has contributed to improving the overall quality of government spending. Through this analysis, we seek to offer a critical evaluation of the performance of the Regional Government in terms of environmental spending and provide a basis for policies that improve both environmental indicators and the quality of spending, benefiting the population of Loreto. This study also presents itself as a valuable guide for future research in related areas and establishes a significant precedent in the analysis of these issues at a regional level.